2017
DOI: 10.1097/md.0000000000006169
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cardiac troponin rise does not modify the prognosis in elderly patients with hip fracture

Abstract: Perioperative myocardial infarction remains a life-threatening complication in noncardiac surgery and even an isolated troponin rise (ITR) is associated with significant mortality. Our aim was to assess the prognostic value of ITR in elderly patients with hip fracture.In this cohort study, all patients admitted between 2009 and 2013 in our dedicated geriatric postoperative unit after hip fracture surgery with a cardiac troponin I determination were included and divided into Control, ITR, and acute coronary syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
0
24
1
1
Order By: Relevance
“…Nevertheless, all participants were informed of (and given the option to refuse) inclusion in the database, which was declared to the French national data privacy authority (Commission Nationale de l'Informatique et des Libertés, Paris, France). Some participants had been included in previous studies . The UPOG care pathway methodology has been described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, all participants were informed of (and given the option to refuse) inclusion in the database, which was declared to the French national data privacy authority (Commission Nationale de l'Informatique et des Libertés, Paris, France). Some participants had been included in previous studies . The UPOG care pathway methodology has been described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Some participants had been included in previous studies . The UPOG care pathway methodology has been described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…82 In non-cardiac, non-vascular surgery, a systematic review based on 11 studies with 2123 patients has shown odds ratios for 30-day and 1 yr mortality of, respectively, 3.53 (95% CI 2.21-5.62) and 2.53 (95% CI 1.20-5.36), and for major adverse cardiac events of 5.92 (95% CI 1.67-20.96) at 30day and 3.00 (95% CI 1.43-6.29) at 1 yr. 83 Age may play a role in the association between elevated troponins and outcome as a relatively small study in elderly patients with hip fracture has shown that isolated troponin I elevation was not associated with adverse outcome while a clinical acute coronary syndrome was. 84…”
Section: Biomarkersmentioning
confidence: 99%